Equations balanced on the previous day |
3 KI + CrCl3 = 3 KCl + CrI3
Db + Pr = DbPr =>
Db + Pr = DbPr
MnO2(S) + H2SO4(l) = Mn(SO4)2(S) + H2O(l) =>
MnO2(S) + 2 H2SO4(l) = Mn(SO4)2(S) + 2 H2O(l)
C6H12O6 + K2MnO4 + H2O = CO2 + MnO2 + KOH =>
C6H12O6 + 12 K2MnO4 + 6 H2O = 6 CO2 + 12 MnO2 + 24 KOH
MnO2(S) + H2SO4(l) = Mn(SO4)2(S) + H2O(l) =>
MnO2(S) + 2 H2SO4(l) = Mn(SO4)2(S) + 2 H2O(l)
KOH + NiCl2 = KCl + Ni(OH)2 =>
2 KOH + NiCl2 = 2 KCl + Ni(OH)2
Cu + O2 + CO2 + H2O = Cu(OH)2CO3 =>
Cu + O2 + CO2 + H2O = Cu(OH)2CO3
Zn(OH)2 = ZnO + H2O =>
Zn(OH)2 = ZnO + H2O
Co(NO3)2 + H2O = CoO + HNO3 =>
Co(NO3)2 + H2O = CoO + 2 HNO3
CaCl2 + KNO3 = Ca(NO3)2 + KCl =>
CaCl2 + 2 KNO3 = Ca(NO3)2 + 2 KCl
Zn(No3)2 + KOH = ZnO + KNo3 + H2O =>
Zn(No3)2 + 2 KOH = ZnO + 2 KNo3 + H2O
MnO2(S) + H2SO4(l) = Mn(SO4)2(S) + H2O(l) =>
MnO2(S) + 2 H2SO4(l) = Mn(SO4)2(S) + 2 H2O(l)
KMnO4 + Na2SO3 + NaOH = K2MnO4 + Na2SO4 + Na2MnO + H2O =>
2 KMnO4 + 4 Na2SO3 + 2 NaOH = K2MnO4 + 4 Na2SO4 + Na2MnO + H2O
TlCl3 + SO3{2-} + H2O = TlCl + SO4{2-} + H{3} + Cl{-} =>
3 TlCl3 + SO3{2-} + H2O = 3 TlCl + SO4{2-} + 2 H{3} + 6 Cl{-}
SiCl4(s) + H2O(l) = SiO2(s) + HCl(g) =>
SiCl4(s) + 2 H2O(l) = SiO2(s) + 4 HCl(g)
Ca10F2(PO4)6(s) + H2SO4(aq) = Ca(H2PO4)2(aq) + CaSO4(aq) + HF(aq) =>
Ca10F2(PO4)6(s) + 7 H2SO4(aq) = 3 Ca(H2PO4)2(aq) + 7 CaSO4(aq) + 2 HF(aq)
NO + HNO3 = N2O4 + H2O =>
2 NO + 4 HNO3 = 3 N2O4 + 2 H2O
PB(NO3)2(aq) + HCl(aq) = PBCl2(s) + HNO3(aq) =>
PB(NO3)2(aq) + 2 HCl(aq) = PBCl2(s) + 2 HNO3(aq)
KNO3 + H2O2 = K2O + NO3 + H2O =>
2 KNO3 + H2O2 = K2O + 2 NO3 + H2O
CaMg(CO3)2 + HNO3 = Ca{+2} + Mg{+2} + NO3{-} + CO2 + H2O =>
CaMg(CO3)2 + 4 HNO3 = Ca{+2} + Mg{+2} + 4 NO3{-} + 2 CO2 + 2 H2O
CO2 + H2O = C4H8O2 + O2 =>
4 CO2 + 4 H2O = C4H8O2 + 5 O2
NH4Cl + NaNO3 = N2 + H2O + NaCl + HCl =>
5 NH4Cl + 3 NaNO3 = 4 N2 + 9 H2O + 3 NaCl + 2 HCl
Sn(s) + HCl(aq) = SnCl2(aq) + H2(g) =>
Sn(s) + 2 HCl(aq) = SnCl2(aq) + H2(g)
MnO2(s) + H2SO4(l) = Mn(SO4)2(s) + H2O =>
MnO2(s) + 2 H2SO4(l) = Mn(SO4)2(s) + 2 H2O
Pb(No3)2(aq) + HCl(aq) = PbCl2(s) + HNo3(aq) =>
Pb(No3)2(aq) + 2 HCl(aq) = PbCl2(s) + 2 HNo3(aq)
MnO2(S) + H2SO4(l) = Mn(SO4)2(S) + H2O(l) =>
MnO2(S) + 2 H2SO4(l) = Mn(SO4)2(S) + 2 H2O(l)
CaCl2 + I2 = CaI2 + Cl2 =>
CaCl2 + I2 = CaI2 + Cl2
Al + O2 = Al2O3 = Sb2S3 + O2 = Sb2O3 + SO2 =>
4 Al + 3 O2 = 2 Al2O3
NaCl + KH2SbO4 = Na2H2Sb2O7 + KCl + H2O =>
2 NaCl + 2 KH2SbO4 = Na2H2Sb2O7 + 2 KCl + H2O
Pb(NO3)2(aq) + Na3PO4(aq) = Pb3(PO4)2 + NaNO3 =>
3 Pb(NO3)2(aq) + 2 Na3PO4(aq) = Pb3(PO4)2 + 6 NaNO3
FeC2O4 + H2O2 + H2C2O4*2H2O + K2C2O4*H2O = K3[Fe(C2O4)3]*3H2O + H2O =>
2 FeC2O4 + H2O2 + H2C2O4*2H2O + 3 K2C2O4*H2O = 2 K3[Fe(C2O4)3]*3H2O + H2O
FeSO4*7H2O + NaOH + NaNO3 = Fe(OH)3 + Na2SO4 + H2O + NH3 =>
8 FeSO4*7H2O + 15 NaOH + NaNO3 = 8 Fe(OH)3 + 8 Na2SO4 + 50 H2O + NH3
MnO2(S) + H2SO4(l) = Mn(SO4)2(S) + H2O(l) =>
MnO2(S) + 2 H2SO4(l) = Mn(SO4)2(S) + 2 H2O(l)
AuCl3 + H2O = Au + HCl + O2 =>
4 AuCl3 + 6 H2O = 4 Au + 12 HCl + 3 O2
Ba(NO3)2(aq) + H2SO4(aq) = BaSO4(s) + HNO3(aq) =>
Ba(NO3)2(aq) + H2SO4(aq) = BaSO4(s) + 2 HNO3(aq)
K2SO4 + AgNo3 = Ag2SO4 + KNo3 =>
K2SO4 + 2 AgNo3 = Ag2SO4 + 2 KNo3
Ba(OH)2(aq) + H2SO4(aq) = BaSO4(s) + H2O(l) =>
Ba(OH)2(aq) + H2SO4(aq) = BaSO4(s) + 2 H2O(l)
MnO2(S) + H2SO4(l) = Mn(SO4)2(S) + H2O(l) =>
MnO2(S) + 2 H2SO4(l) = Mn(SO4)2(S) + 2 H2O(l)
Al2(SO4)3(aq) + NaOH(aq) = Al(OH)3(s) + Na2SO4(aq) =>
Al2(SO4)3(aq) + 6 NaOH(aq) = 2 Al(OH)3(s) + 3 Na2SO4(aq)
BaCl2(aq) + Al2(SO4)3(aq) = BaSO4(s) + AlCl3(aq) =>
3 BaCl2(aq) + Al2(SO4)3(aq) = 3 BaSO4(s) + 2 AlCl3(aq)
Cu(s) + HNO3(l) = NO2(g) + H2O(l) + Cu(NO3)2(aq) =>
Cu(s) + 4 HNO3(l) = 2 NO2(g) + 2 H2O(l) + Cu(NO3)2(aq)
(NH4)2SO4 + HNO3 = NH4NO3 + H2SO4 =>
(NH4)2SO4 + 2 HNO3 = 2 NH4NO3 + H2SO4
MnO2(S) + H2SO4(l) = Mn(SO4)2(S) + H2O(l) =>
MnO2(S) + 2 H2SO4(l) = Mn(SO4)2(S) + 2 H2O(l)
Ba(OH)2 + HNO3 = H3O{+} + OH{-} + Ba(NO3)2 =>
Ba(OH)2 + 2 HNO3 = H3O{+} + OH{-} + Ba(NO3)2
H3PO4 + Mg(OH)2 = Mg3(PO4)2 + H2O =>
2 H3PO4 + 3 Mg(OH)2 = Mg3(PO4)2 + 6 H2O
(NH4)2SO4 + Ba(OH)2 = BaSO4 + NH4OH =>
(NH4)2SO4 + Ba(OH)2 = BaSO4 + 2 NH4OH
EDTA + Ni(NO3)2 = EDTANO3 + Ni =>
2 EDTA + Ni(NO3)2 = 2 EDTANO3 + Ni
CH4 + O2 = CO2 + H2O =>
CH4 + 2 O2 = CO2 + 2 H2O
MnO2(S) + H2SO4(l) = Mn(SO4)2(S) + H2O(l) =>
MnO2(S) + 2 H2SO4(l) = Mn(SO4)2(S) + 2 H2O(l)
FeCl2 + ClF = FeF3 + Cl2 =>
2 FeCl2 + 6 ClF = 2 FeF3 + 5 Cl2
Balance the equation of any chemical reaction
Equations balanced on the previous day |
Equations balanced on 01/04/25
Equations balanced on 02/03/24
Please let us know how we can improve this web app.